Chorknaben und andere Gymnasiasten - Determinanten musikalischer Aktivitäten an Gymnasien mit unterschiedlichen Schulprofilen - Fritzsche, Eva; Kröner, Stephan; Pfeiffer, Wolfgang (Journal for educational research online, 2011)
Wovon hängt es ab, wie musikalisch aktiv Gymnasiastinnen und Gymnasiasten sind? Der Theorie des geplanten Verhaltens zufolge sollten der intrinsische Wert als Aspekt der Einstellung, die musikalische Affinität von Freunden und Eltern als Aspekt der subjektiven Norm und das musikalische Selbstkonzept als Aspekt der wahrgenommenen Verhaltenskontrolle relevante Prädiktoren musikalischer Aktivitäten sein. Ebenfalls relevant dürfte die Musikbezogenheit des Profils der besuchten Schule sein. Dies wurde anhand von N = 2016 musikalisch aktiven Gymnasiasten überprüft. Mittels Mehrgruppen-Strukturgleichungsmodellen wurden Jungen an nicht ausgeprägt musischen Gymnasien als Referenzgruppe mit Mädchen derartiger Gymnasien und mit Jungen an ausgeprägt musischen Gymnasien verglichen. Erwartungsgemäß wiesen die Jungen an ausgeprägt musischen Gymnasien gegenüber der Referenzgruppe im Mittel höhere musikalische Affinitäten von Freunden und Eltern und umfangreichere musikalische Aktivitäten auf. Innerhalb der Gruppen zeigten sich uneinheitliche Effekte der Prädiktoren. Implikationen für Effekte von Schulprofilen auf die Förderung musikalischer Aktivitäten werden diskutiert. <br

Differenzierung im Musikunterricht - Pfeiffer, Wolfgang (Heterogene Klassen – Differenzierung in Schule und Unterricht, 2011)

Domain-Specificity of Educational and Learning Capital: A Study With Musical Talents - Reutlinger, Marold; Pfeiffer, Wolfgang; Stoeger, Heidrun; Vialle, Wilma; Ziegler, Albert (Frontiers in Psychology, 2020)
The Education and Learning Capital Approach (ELCA) has been widely used to investigate talent development. A research gap is the implicit consideration of the domain specificity of educational and learning capital. In an empirical study with 365 school students we investigated the domain specificity of the approach for the domains of school learning and learning to play a musical instrument. At the beginning of the school year, students filled out a version of the Questionnaire for Educational and Learning Capital (QELC) for both domains and also responded to other domain-related measures (self-efficacy, grades). Six weeks later, students filled out a learning diary for 1 week in which they reported their activities on an hourly basis and responded to questions concerning these activities. Based on the Sociotope Approach this procedure helped to identify times in which students actually practiced their musical instrument, times that students could potentially practice their musical instrument (objective action space), and times that students would be expected to practice their musical instrument (normative action space). Three hypotheses were tested and could be supported. First, the availability of educational and learning capital for school learning and learning an instrument differed. Second, a confirmatory factor analysis supported the factorial validity of the domain-specific capital measurements. Third, domain-congruent correlations were mostly higher than domain-incongruent correlations, i.e., the availability of educational and learning capital for school learning correlated more closely with variables related to school learning than with variables related to learning a musical instrument. Similarly, the availability of the capitals for learning a musical instrument correlated more closely with variables related to learning a musical instrument.
CRIS-Team Scopus Importer:2020-10-23
Keywords: domain specificity; educational capital; learning capital; music; talent development

Jugend – Musik – Sozialisation: Perspektive der Musikpädagogik. - Pfeiffer, Wolfgang (Handbuch Jugend - Musik - Sozialisation, 2013)
Keywords: Musikdidaktik; Musikpädagogik; Geschichte der Musikpädagogik; Singen; Wandervogel; Jugendkulturen; Musikunterricht; Ziele von Musikunterricht; Jugend und Musik; Musik in der Schule; Musik und Kompetenz

Kapitale in der Musik - Straßer, Sabrina; Groß, Carolin; Pfeiffer, Wolfgang; Ziegler, Albert (Journal für Begabtenförderung, 2013)

Klasse.im.puls –bayerischer Rockpreis für ein Musikprojekt - Pfeiffer, Wolfgang (Praxis des Musikunterrichts, 2015)
Keywords: klasse.im.puls; Klassenmusizieren; Musikklasse

Klasse.im.puls – die bayrische Antwort auf Jeki - Pfeiffer, Wolfgang (AfS-Magazin, 2011)
Keywords: Klassenmusizieren; Musikklasse

klasse.im.puls – ein Projekt steht für gelingende Schulentwicklung - Beissel, Evelyn; Fichte, Tobias; Pfeiffer, Wolfgang; Seufert, Ilona (Musikunterricht 2 - Bildung, Musik, Kultur - Horizonte öffnen, 2015)
Keywords: Klassenmusizieren; klasse.im.puls; Schulentwicklung

Medienbildung in schulischen Kontexten. Erziehungswissenschaftliche und fachdidaktische Perspektiven - Pirner, Manfred; Pfeiffer, Wolfgang; Uphues, Rainer (kopaed, 2013)

Medienbildung in schulischen Kontexten. Erziehungswissenschaftliche und fachdidaktische Perspektiven. Zur Einführung - Pirner, Manfred; Pfeiffer, Wolfgang; Uphues, Rainer (Medienbildung in schulischen Kontexten. Erziehungswissenschaftliche und fachdidaktische Perspektiven., 2013)

Musical elite gymnasia as learning environments and settings for personality development in secondary students? The case of musical self-concept. - Fritzsche, Eva; Pfeiffer, Wolfgang; Kröner, Stephan (Psychological Test and Assessment Modeling, 2015)
Elite gymnasia with a main focus on musical education are special institutional learning environments for the students attending those schools: Their curricula differ considerably from those of non-specialized schools regarding the emphasis that is placed on musical activities. Thus, if effects of intensive musical education on personality development proposed in musical education research are to be found, then examining students from such elite schools seems pertinent. However, beyond institutional impact, effects of variables from the students’ individual learning environment are to be expected. Thus, reanalysing data from Bernecker, Haag and Pfeiffer (2006), we investigated effects of both the institutional and the individual learning environment on different facets of the self-concept of ability with n = 509 students from 91 classes including class-levels 5 to 10 (corresponding to an age of 10 to 16 years). Classes we re located either at musical elite gymnasia providing intensive musical education and including the opportunity to participate in an internationally recognised choir or at non-specialized gymnasia without such an elite musical profile. As expected, multilevel analyses revealed strong effects of school type (i.e., institutional effects) on musical activities. However, in line with Schellenberg (2006), our results did not provide evidence either for substantial institutional effects on the musical self-concept, or for such effects on the academic or general self-concept. Rather, variance in self-concept facets could better be explained via aspects of the individual learning environment or by personal characteristics like school grades or the intrinsic value of musical activities. The implications for potential effects of attending a musical elite gymnasium on personality development as well as avenues for further research are discusse

Musicalproduktion in der Schule : Tipps und Tricks rund um die Aufführung von Musicals - Pfeiffer, Wolfgang (Zwischen Rockklassikern und Eintagsfliegen : 50 Jahre populäre Musik in der Schule, 2010)

Musik-Theater, ein Großprojekt an der Schule - Pfeiffer, Wolfgang (Schultheater : Wahrnehmung, Gestaltung, Spiel, 2011)
Keywords: Musiktheater; Musical; Schulentwicklung

Nachhaltiges Lernen in Musik: Musikalische Grundschule und klasse.im.puls. - Beissel, Evelyn; Pfeiffer, Wolfgang (Netzwerke. Theorien und Praxen kultureller Bildung, 2015)
Keywords: Klassenmusizieren; Musikklasse; Klasse.im.puls; Musikalische Grundschule